The golden wasp - Abbott, Tony; Jessell, Tim (Scholastic New York, 2000)
"A hidden door. A magical staircase. Discover the world of Droon!"Eric, Julie, and Neal have a big problem on their hands. Galen the wizard had warned them never to bring anything from Droon into the Upper World. But Julie has brought a bracelet by mistake, and it's turned Eric's dad into a ghost in Droon! Now the kids must find him. If they don't, he'll end up in the Land of the Lost- forever